Who is coming back to prison? Emerging adulthood and the challenges associated with desistance from crime - Fortin-Dufour, Isabelle (International journal of comparative and applied criminal justice, 2025)
Emerging adulthood is a period involving dramatic change and many life transitions. Justice-involved individuals experiencing these transitions are statistically more likely to engage in criminal behaviours and to return into incarceration and are therefore frequently targeted for intervention by the criminal justice system. We also know that the emerging adulthood is a period of life transitions during which most young offenders eventually desist from crime, albeit at different paces. The current study is set to better understand factors that could accelerate the process of desistance. The current study presents findings from a cohort of 1,770 young men incarcerated in the province of Quebec, Canada, and aims at identifying factors more often associated with young adult recidivism or factors that facilitate their desistance. The findings show that young adult men with substance abuse problems, endorsing procriminal attitudes who are struggling with marital and familial problems, are more likely to return to prison. The implications of these findings for correctional intervention programmes are discussed.